2022
DOI: 10.5552/crojfe.2023.1743
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Felling Techniques Considering Stump-Height-Related Timber Value Loss

Abstract: Harvest from plantations can provide both industrial wood and forest residues for bioenergy, including stumps. The literature suggests that the choice of cutting system can affect the division between industrial wood recovery and remaining stump volume. In this study, two felling techniques - motor-manual chainsaw and feller-buncher, were compared based on stump-height-related timber value loss for four ground slope classes: high, medium, low, and flat. The economic value loss of wood material for three produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The measurements for stumps in the chainsaw study averaged 36.50 cm, 17.16 cm, and 0.02 m 3 . The results indicate that chainsaw cutting led to a stump height 50% greater than feller-buncher cutting [21]. Furthermore, the trimming tool study showed an 8.47 cm higher stump level compared to the fellerbuncher site study [21].…”
Section: Stump Wastementioning
confidence: 78%
See 2 more Smart Citations
“…The measurements for stumps in the chainsaw study averaged 36.50 cm, 17.16 cm, and 0.02 m 3 . The results indicate that chainsaw cutting led to a stump height 50% greater than feller-buncher cutting [21]. Furthermore, the trimming tool study showed an 8.47 cm higher stump level compared to the fellerbuncher site study [21].…”
Section: Stump Wastementioning
confidence: 78%
“…The results indicate that chainsaw cutting led to a stump height 50% greater than feller-buncher cutting [21]. Furthermore, the trimming tool study showed an 8.47 cm higher stump level compared to the fellerbuncher site study [21]. The discrepancy in the height of the stumps was very similar to a study carried out by [22], who found that trees cut with a feller-buncher had an average stump height that was 8.8 cm lower than those cut with a chainsaw.…”
Section: Stump Wastementioning
confidence: 89%
See 1 more Smart Citation